Affective teaching can you measure up? - Sonnier, Isadore L. (Education quarterly.)
Some cause-and-effect relationships were proposed concerning the nature of individual differences among learners and teachers and how different teachers implement different kinds of activities in their teaching strategies. Strategies emphasizing the cognitive domain were suggested to have significant relationships and align well with the right hemispheric processes of the human brain. The instrument was offered to remove the ever present subjectivity when measuring teaching results in the affective domain. This instrument can be used by any teacher to determine how closely aligned a certain teaching strategy, subject content, or procedure is with desirable affective outcomes as perceived by the learner, educational accountability at the grassroots level.